Behaviour-change intervention in a multicentre, randomised, placebo-controlled COPD study: methodological considerations and implementation. Issue 4 (4th April 2016) - Bourbeau, Jean; Lavoie, Kim L; Sedeno, Maria; De Sousa, Dorothy; Erzen, Damijan; Hamilton, Alan; Maltais, François; Troosters, Thierry; Leidy, Nancy
Abstract : Introduction: Chronic obstructive pulmonary disease is generally progressive and associated with reduced physical activity. Both pharmacological therapy and exercise training can improve exercise capacity; however, these are often not sufficient to change the amount of daily physical activity a patient undertakes. Behaviour-change self-management programmes are designed to address this, including setting motivational goals and providing social support. We present and discuss the necessary methodological considerations when integrating behaviour-change interventions into a multicentre study. Methods and analysis: PHYSACTO is a 12-week phase IIIb study assessing the effects on exercise capacity and physical activity of once-daily tiotropium+olodaterol 5/5 µg with exercise training, tiotropium+olodaterol 5/5 µg without exercise training, tiotropium 5 µg or placebo, with all pharmacological interventions administered via the Respimat inhaler. Patients in all intervention arms receive a behaviour-change self-management programme to provide an optimal environment for translating improvements in exercise capacity into increases in daily physical activity. To maximise the likelihood of success, special attention is given in the programme to: (1) the Site Case Manager, with careful monitoring of programme delivery; (2) the patient, incorporating patient-evaluation/programme-evaluation measures to guide the Site Case Manager in the self-management intervention; and (3) quality assurance, to help identify and correct any problems or shortcomings in programme delivery and ensure the effectiveness of any corrective steps. This paper documents the comprehensive methods used to optimise and standardise the behaviour-change self-management programme used in the study to facilitate dialogue on the inclusion of this type of programme in multicentre studies. Ethics and dissemination: The study has been approved by the relevant Institutional Review Boards, Independent Ethics Committee and Competent Authority according to national and international regulations. The results of this study will be disseminated through relevant, peer-reviewed journals and international conference presentations. Trial registration number: NCT02085161.